Awareness and Practices on Disaster Risk Preparedness of Maritime Students - Abegail P. Panase; Ma. Elena Y. Doruelo (Philippine Social Science Journal, 2020)
Disaster preparedness is a measure in which individuals or groups developed plans, allocated resources, and established procedures for implementing the program in case of emergency. Alarming cases of maritime disasters have occurred in the Philippines in the past years. These incidents have created damage to property and loss of lives. They have placed the credibility of maritime officers and the maritime industry in question. These cause a catastrophic impact on the environment as well as on marine life. Hence, the paper describes the level of awareness and extent of the practice of disaster risk preparedness of maritime students of St. Therese MTC Colleges, School Year 2019-2020 at Iloilo City. Likewise, it explores the awareness and extent practices of maritime students. Moreover, it determines the correlation among awareness and extent practices on disaster risk preparedness of maritime students.